Are Devaluations Contractionary? - Edwards, Sebastian (The Review of Economics and Statistics, 1986)
Recently a number of authors have criticized the role of devaluations in traditional stabilization programs.It has been argued that, contrary to the traditional view, devaluations are contractionary, and generate a decline in aggregate output.In spite of the renewed theoretical interest in the possible contractionary effects of devaluations, the empirical evidence on the subject has been quite sketchy.In this paper the Khan and Knight (1981) model is extended to empirically address the issue of contractionary devaluations.The extended model considers the effect of money surprises, fiscal factors, terms of trade changes and devaluations on the level of real output.The results obtained, using a variance components procedure on data for 12 developing countries, provide some support to the short-run contractionary devaluation hypothesis; the results obtained indicate that in the short run a devaluation will generate a decline in aggregate output.It is also found that after one year a devaluation will have an expansionary effect on output.The evidence suggests that in the long run, devaluations will have no effect on output.